1992
DOI: 10.1364/ol.17.000833
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bragg reflectors prepared by a single excimer pulse

Abstract: Narrow-line, permanent Bragg reflection gratings have been created in Ge-doped silica-core optical fibers by interfering beams of a single 20-ns pulse of KrF excimer laser light. Of the fibers studied, the highest reflectance value of ~2% was observed with a linewidth (FWHM) of 0.1 nm, which corresponds to a 2-mm grating length with an index modulation of ~3 x 10(-5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(30 citation statements)
references
References 7 publications
0
26
0
1
Order By: Relevance
“…Askins et al reported that the fiber Bragg gratings could be created in GeSiO 2 fibers by interfering beams of a single pulse of KrF laser. 33) Therefore, Figure 9 shows that the intensity of luminescence decreased to less than half upon irradiation with the KrF laser.…”
Section: Bandtoband Excitationmentioning
confidence: 94%
“…Askins et al reported that the fiber Bragg gratings could be created in GeSiO 2 fibers by interfering beams of a single pulse of KrF laser. 33) Therefore, Figure 9 shows that the intensity of luminescence decreased to less than half upon irradiation with the KrF laser.…”
Section: Bandtoband Excitationmentioning
confidence: 94%
“…On the experimental point of view, one of the difficulties for interferometry in the DUV range is due to the low coherence of available DUV lasers. As an example, typical coherence of ArF lasers is limited to a few hundreds of microns, which justifies efforts to develop specific experimental setup for short wavelengths (Figure 1 (Bourov et al, 2004), b) Lloyd setup (Raub & Brueck, 2003) and c) achromatic holographic configuration (Yen et al, 1992) Holographic grating formation has been proposed (Askins et al, 1992;Archambault et al, 1993). However, in all cases, it has been necessary to increase the spatial coherence and decrease the spectral emission band width of excimer lasers, which considerably increase the laser system complexity and demonstrations have been mostly done with 248 nm lasers.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Multiple gratings are of specific interest in sensor systems in order to allow quasi-distributed sensing and for achieving sensor multiplexing. So-called draw tower gratings, which are recorded by single pulses during the fiber drawing process, have been developed especially for this purpose [4][5][6][7]. These examples show the need for specific developments adapted to the needs of fiber sensor applications.…”
Section: Introductionmentioning
confidence: 99%